Unique hip and stifle extensor muscle patterns in the Eurasian lynx, Lynx lynx (Carnivora: Felidae) - Viranta, Suvi; Holmala, Katja; Laakkonen, Juha (Journal of Morphology, 2021)
The Eurasian lynx (Lynx lynx) is a medium-sized felid, with a tendency to hunt for prey larger than itself. We studied the lynx hindlimb musculoskeletal anatomy in order to determine possible anatomical adaptations to hunting large prey. In our previous work, we had found characters of both large and small felids in the lynx forelimb. The crouched limbs, typical of all felids, increase the energy demands for the antigravity muscles during locomotion. As a powerful pounce is required for the smaller felid to bring down large prey, strong hindquarters may be needed. We hypothesized that the muscle attachments are more mechanically advantageous and muscles heavier in the lynx as compared to other felids to compensate for the energy requirements. In support of this, we found unique patterns in the hindlimb musculature of the lynx. Insertion of the m. gluteus medius was large with a short moment arm around the hip joint, providing mechanical disadvantage, but rapid movement. The musculus vastus medialis was relatively heavier than in other felids emphasizing the role of the m. quadriceps femoris as a powerful stifle extensor. The extensor muscles support the crouched hind limbs, which is crucial when tackling large prey, and they are also responsible for the swift powerful pounce brought by extending the hindlimbs. However, we cannot rule out the possibility the characters are shared with other Lynx spp. or they are adaptations to other aspects of the locomotor strategy in the Eurasian lynx. Peer reviewed